The Bisitun Inscription of Darius the Great. Aramaic Version. I - Greenfield, Jonas С. (1982)
Introduction by B. Porten, Handcopy by Ada Yardeni; Corpus inscriptionum iranicarum. Part I: Inscriptions of Ancient Iran. Vol. V: The Aramaic Versions of the Achaemenian Inscriptions. Texts I; Published on behalf of Corpus inscriptionum iranicarum by Lund Humphries. £30.00.